Norway Moving Away from Populist Education? - Welle-Strand, Anne; Tjeldvoll, Arild; Thune, Taran (Acta Paedagogica Vilnensia, 2004)
Which indications are found of Norway moving away from welfare state populist education into the mainstream of educational globalisation? Contrasting the legacies with the current ideological and political changes certain educational consequences are identified. Effects on governance and funding, structure, curriculum and the level of participation and equality are seen. Certain dilemmas of "double talk" are found. Simultaneously with the country’s slow adaptation to current international mainstream there are loud expressions of the old urban socialist and the rural populist values. The speed of change is expected to be slow due to the fortunate offshore oil economy.